Midnight harbor - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay., 2024)
When his Aunt Amelia, his closest friend and greatest supporter, passes away, leaving him her home in Miramar, classical guitarist Ian Hart uses this opportunity to reflect and move forward after a scandal destroyed his career but instead finds himself drawn to another newcomer, artist Kari Langham, who changes everything.